Bioimpedance spectroscopy and volumetry in the immediate/short-term monitoring of intensive complex decongestive treatment of lymphedema. (October 2020) - Cavezzi, Attilio; Urso, Simone U; Paccasassi, Stefania; Mosti, Giovanni; Campana, Fausto; Colucci, Roberto
Aims: To assess (a) immediate/short-term outcomes of intensive complex decongestive treatment of lower limb lymphedema, by means of bioimpedance spectroscopy and tape measurement-based volumetry, and (b) correlation between these two methods. Patients and methods: Cohort study on patients affected by unilateral primary or secondary lymphedema, stage II or III. Patients underwent complex decongestive treatment (manual and electro-sound lymphatic drainage, compression bandage, exercises, low-carb nutrition, and dietary supplements) for six days. Before (D0), three and six days after complex decongestive treatment (D3 and D6), volumetry and bioimpedance spectroscopy data of the total limb and lower leg were collected. Statistical analysis was applied to pre–post treatment outcomes and to the volumetry/bioimpedance spectroscopy correlation. Results: Forty-one patients (15 males and 26 females, mean age: 50.7 years) were included. A progressive improvement of volumetry and bioimpedance spectroscopy figures was recorded. Total limb and leg volumetry (mean value in cc) was, respectively, 11, 072.9 and 3150.8 at D0, 10, 493 (−5.2%, p = 0.001) and 2980.2 (−5.4%, p < 0.001) at D6. Total limb lymphatic index at D0 and D6 was 18.9 and 14.8 (−21.5%, p < 0.001). Total limb resistance at D0, D3, and D6 was 200.4, 225.7, and 237.5 (+18.5%, p < 0.001), respectively; leg resistance at D0 and D6 was 117.5 and 150 (+27.7%, p < 0.001), respectively. Total limb reactance at D0, D3, and D6 was 12.2, 15, and 16.6 (+35.5%, p < 0.001), respectively. Leg reactance at D0 and D6 was 7.7 and 11.5 (+ 49.6%, p < 0001), respectively. Correlation volumetry/bioimpedance spectroscopy data were (a) total limb volumetry/resistance rho = −0.449, p < 0.01; volumetry/reactance rho=−0.466, p < 0.01; volumetry/lymphatic index rho = 0.581, p < 0.01; (b) leg volumetry/resistance rho=−0.579, p < 0.01; volumetry/reactance rho=−0.469, p < 0.01; volumetry/lymphatic index rho = 0.466, p < 0.05. Conclusions: Complex decongestive treatment on lymphedematous limbs was effective at short term; both volumetry and bioimpedance spectroscopy showed a statistically significant improvement. Resistance and reactance increase, with lymphatic index decrease, correlated with volumetry decrease. Bioimpedance spectroscopy proved to help to assess fluid decrease and the tissue-related parameters variations.